Vaccine safety beliefs in the state of Alaska - R. David Parker; Jennifer A. Meyer (Elsevier, 2024)
Objectives: Identifying the key factors associated with vaccine hesitancy remains a challenge as has been highlighted throughout the COVID-19 vaccine roll out and pandemic. The aim of this study was to determine characteristics associated with vaccine safety and compare perceived safety by vaccine. Our hypothesis is that vaccine safety perception will vary by vaccine with COVID-19 as ranked lowest for safety. Study design: Cross sectional. Methods: A statewide sample (n = 1024) responded to an online 28-point questionnaire via anonymous linked invitation. Results: Among the eight vaccines assessed, COVID-19 had the lowest perceived safety (53.13%) followed by human papillomavirus HPV (63.38%). A binomial logistic regression assessed COVID-19 vaccine safety beliefs (safe v not safe) finding age, political orientation, and perceived safety of certain vaccines as statistically significant. As age increased by year, vaccine safety beliefs increased. Persons who identified as conservative demonstrated less belief in vaccine safety than all other groups. Among persons who did not perceive the COVID-19 vaccine as safe, 65.8% believed chicken pox was safe, 63.3% and 61.1% perceived hepatitis A& B were safe. Conclusions: These findings demonstrate that vaccine safety beliefs differ by vaccine and that persons who do not believe in the safety of the COVID-19 are not exclusively against all vaccines. Understanding factors that increase vaccine safety by vaccine could assist in developing an intervention which could increase belief in safety for all vaccines.